Utilization of Literature Based Math in Developing Didactic Designs for Students' Mathematical Understanding in the Decimal Concept - Wida Rachmiati; Helnanelis Helnanelis; Juhji Juhji (UIN Siber Syekh Nurjati Cirebon, 2020)
AbstractThis research is motivated by learning barriers and low understanding of the mathematical students of Madrasah Ibtidaiyah on the concept of decimal fraction. The purpose of this research is to determine the effective learning technique for decimal fraction by using storybook. This type of research uses didactical design research which includes the stages of prospective analysis, metapedia didactic analysis, and re-prospective analysis. The draft of the design applied to twenty-eight students' sixth grade of Madrasah Ibtidaiyah Nurul Hidayah Kadupandak Serang City. Observation sheets, interviews, and test comprehension were used as a data collection instrument for implementation execution. Didactic design using literature based math was made through one revision and it consist of eight steps. The results showed that the implementation of didactical design using literature based math can help students build their mathematical understanding of the decimal concept. It can be seen from the reduced percentage of students' errors in solving comprehension test questions from 71.6% to 11.6%. Therefore, for elementary teacher who has storybooks related to mathematical concepts are advised to try the eight learning steps developed in this study.Keywords: literature-based math, didactic designs, students' mathematical understanding.AbstrakPenelitian ini dilatarbelakangi oleh hambatan belajar dan pemahaman matematis siswa Madrasah Ibtidaiyah yang masih rendah pada konsep pecahan desimal. Tujuan dari penelitian ini adalah untuk mengetahui efektifitas teknik pembelajaran pecahan desimal dengan menggunakan buku cerita. Jenis penelitian yang digunakan adalah penelitian desain didaktis yang meliputi tahapan analisis prospektif, analisis metapeda didaktik, dan analisis re-prospektif. Rancangan desain didaktis diterapkan pada 28 (dua puluh delapan) siswa kelas VI (enam) Madrasah Ibtidaiyah Nurul Hidayah Kadupandak Kota Serang. Lembar observasi, wawancara, dan tes pemahaman digunakan sebagai instrumen pengumpulan data dalam penelitian. Desain didaktis dengan menggunakan matematika berbasis literatur dibuat melalui satu kali revisi dan terdiri dari delapan langkah. Hasil penelitian menunjukkan bahwa penerapan desain didaktis dengan menggunakan matematika berbasis literatur dapat membantu siswa dalam membangun pemahaman matematika tentang konsep desimal. Hal tersebut terlihat dari berkurangnya persentase kesalahan siswa dalam menyelesaikan soal tes pemahaman dari 71,6% menjadi 11,6%. Oleh karena itu, bagi guru sekolah dasar yang memiliki buku cerita yang berkaitan dengan konsep matematika disarankan untuk mencoba delapan langkah pembelajaran yang dikembangkan dalam penelitian ini.Kata kunci: matematika berbasis literatur, desain didaktis, pemahaman matematika siswa.